Criminal Liability for B3 Waste Dumping Companies in East Jawa from The Perspective of Ecological Justice: Pertanggungjawaban Pidana Perusahaan Pembuangan Limbah B3 di Jawa Timur dari Perspektif Keadilan Ekologis - Rosnawati , Emy; Fatah , Abdul; Multazam , Mochammad Tanzil (Procedia of Social Sciences and Humanities, 2022)
A good and healthy living environment is a constitutional right of every citizen. Guarantee and protection of the good and healthy living environment are stipulated in Article 28H paragraph (1) and Article 33 paragraph (4) of The 1945 Constitution of the Republic of Indonesia (UUD 1945). Apart from being regulated in the state constitution (UUD 1945), the protection and management of a good and healthy living environment in Indonesia are also technically regulated in other constitution, namely Law No. 32/2009 on Environmental Protection and Management. The purpose of this research is to examine if the criminal liability of B3 waste dumping companies in East Java is already in accordance with the concept of ecological justice. This research uses the method of sociological juridical. By not stopping the company's activities to store B3 waste with open dumping, the environment is constantly damaged, and it causes the quality of the environment to decline, so that the criminal liability cannot guarantee sustainable development as is the concept of environmental justice. The conclusion of this research is that criminal liability for B3 waste dumping companies in East Java is not yet in accordance with the concept of ecological justice.